Familial High Plasminogen Activator Inhibitor with Hypofibrinolysis, a New Pathophysiologic Cause of Osteonecrosis? - Glueck, C J; Glueck, H I; Mieczkowski, L; Tracy, T; Speirs, J; Stroop, D (Thrombosis and Haemostasis, 1993)
In a 29 year old white male with osteonecrosis of both hips and a shoulder, and in his family, we measured basal and stimulated (10 min cuff venous occlusion at 100 mgHg) fibrinolytic activity to determine whether low fibrinolytic activity might be heritable and etiologically associated with osteonecrosis. The proband’s basal tPA-Fx was low, 0.08 IU/ml (normal 0.11-1.94), tPA-Ag was normal (11.6 ng/ml), plasminogen activator inhibitor activity (PAI-Fx) was very high, 119 U/ml (normal 3.5-27), as was his plasminogen activator inhibitor antigen (PAI-Ag), 202 ng/ml (normal 3.2-37.1). The proband’s basal PAI-Fx (119) and PAI-Ag (202) were respectively 6 and 13 standard deviations greater than the mean PAI-Fx (17 ± 15 U/ml) and the mean PAI-Ag (25 ± 13 ng/ml) in 172 concomitantly studied hyperlipidemic men. Alpha-2 antiplasmin, fibrinogen, plasminogen and Lp(a) were normal. Despite lowering TG to 301 mg/dl, basal tPA-Fx remained low, 0.05; PAI-Fx and PAI-Ag remained very high (109 and 191). Following venous occlusion, stimulated tPA-Fx remained very low, 0.1 (normal 2.3-11.3), but tPA-Ag rose normally to 17 (normal 8.4-31.4); stimulated PAI-Fx and PAI-Ag were very high, 134 and 223, (normal PAI-Fx 3.6-24, PAI-Ag 12-96). Stimulated D-dimer was < the 10th percentile, 0.084 μg/ml. With such high PAI-Fx available to bind tPA, occlusionstimulated tPA-Fx could not rise, and fibrinolysis could not be initiated. Neither diseases nor drugs could explain the high PAI-Fx and PAI-Ag, low tPA-Fx, or osteonecrosis. The proband’s father, mother, and sister had very high basal PAI-Ag (240, 69, 66 ng/ml), high basal PAI-Fx (24, 24, 35 U/ml), and normal basal tPA-Fx (0.6, 1.0, and 0.2 IU/ml). Basal PAI-Ag, PAI-Fx, and tPA-Fx were normal in the proband’s son (13, 12, 0.3). The proband’s very high PAI-Fx and PAI-Ag appeared to be inherited, possibly as an autosomal dominant trait, producing hypofibrinolysis. We speculate that his osteonecrosis was caused by familial hypofibrinolysis mediated by high PAI, with subsequent inability to activate fibrinolysis, resulting in inadequate lysis of venous thrombi in bone, impaired bone venous circulation, and venous hypertension of bone characteristic of osteonecrosis.